Analisis Distribusi Waktu Kerusakan Mesin pada Lini Produksi Cylinder Comp K-XX (Studi Kasus: PT XYZ) - Gidion Karo-Karo; Panca Jodiawan (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Technologies development has led industries to the usage of machinery. It certainly will give more output to increase the responsiveness of customers’demand. However, as a machine has a lot of advantages, it will also bear some disadvantages which one of them is downtime issue. A big amount of downtime in a machine will decrease the production overall efficiency. Efforts have been made since a long time ago to overcome downtime issue which one of them that is frequently used is preventive maintenance. Preventive maintenance planning can be implemented if reliability assessment has been made on the related machine, so the preventive maintenance interval can be determined. At XYZ’s corporation, there are two machines which were determined as the object for these report, RB037 and HO012P. Time Between Failure (TBF) of RB037 follows the normal distribution with mean equals to 171,22, standard deviation equals to 107,003, and has an increasing hazard rate. In the other side, HO012P follows the Weibull distribution with shape characteristics equals to 3,067 and scale characteristics equals to 577,96 and has an increasing hazard rate too. Between these two machines, RB037 has bigger hazard rate than HO012P, so further preventive maintenance should be planned well.Keywords: Downtime, Preventive Maintenance, Reliability.